Deformation properties of remolded loess compacted via vertical vibration compaction method - Yingjun Jiang; Kejia Yuan; Jiangtao Fan; Chenfan Bai; Wei Zhang; Jinshun Xue (Journal of Traffic and Transportation Engineering (English ed. Online))
To investigate the deformation properties of remolded loess subgrade under long-term cyclic dynamic loading, remolded loess specimens compacted via vertical vibration compaction method were produced and some factors influencing elastic strain and cumulative plastic strain, which include the number of vibration cycles, depth, and water content, have been investigated. A prediction model for cumulative plastic deformation was established. In addition, the collapsible deformation properties of remolded loess were investigated. Results indicate that the elastic strain and plastic strain are decreased with increasing vibration cycles and depth and finally tend to be stable when the number of vibration cycles is more than 2000 and the depth exceeds 2.5 m. The elastic strain and cumulative plastic strain of compacted loess are increased by 7.2% and 13.0%, respectively, when the water content increases by 1.0%. The cumulative plastic deformation of remolded loess follows a logarithmic distribution. The elastic deformation and cumulative plastic deformation of loess subgrade are far less than the demands for elastic deformation and post-construction settlement of subgrade. As the compaction coefficient and water content are increased by 1.0%, the collapsibility coefficient of compacted loess is decreased by an average of 13.7% and 14.5%. Such investigations can prevent subgrade diseases and ensure the safety of subgrade filled with loess soils.